PENGEMBANGAN WEB APLIKASI SISTEM RESERVASI GREENSA INN DAN TRAINING CENTER MENGGUNAKAN FRAMEWORK BOOTSTRAP 5 - Al-Izzi, Ahmad Kemal; Permadi, Andhy; Kunaefi, Anang (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2025)
This study aims to develop a web-based meeting room reservation system at Greensa Inn & Training Center, part of the Business Development Center of UIN Sunan Ampel Surabaya. The system development used the Waterfall methodology with Laravel 10 for the back-end and Bootstrap 5 for the front-end. The research methods included system design using Unified Modeling Language (UML) and Entity Relationship Diagram (ERD), as well as user-friendly interface design. The result of this system development is improved efficiency and transparency in the meeting room reservation process, allowing users to view room availability in real-time, make reservations, and manage bookings more easily. This system also supports the management and monitoring of meeting room usage by the administrators, thus enhancing accuracy and reducing schedule conflicts. This project not only provides valuable practical experience for students but also offers an innovative solution that benefits the operational efficiency of Greensa Inn & Training Center.